Synthesis and Characterization of Novel Nematic Liquid Crystal Compound - Mohammed Obaid Hasan (Journal of Global Pharma Technology, 2018)
A series of N1-(4'-((4-(alkyloxy)benzylidene)amino)-[1,1'-biphenyl]-4-yl)-N4-(4'-((Z)-(4-(alkyloxy)benzylidene)amino)-[1,1'-biphenyl]-4-yl)terephthalamides were synthesized by thermal condensation reaction of N1,N4-bis(4'-amino-[1,1'-biphenyl]-4-yl) terephthalamide with 4-(alkoxy) benzaldehydes in absolute ethanol at reflux condition. The structure of the synthesized compounds were elucidated by FT-IR spectral data and determining the M.Ps, and element content (C.H.N %). Their liquid crystal properties were studied by measuring the values of the phase transition temperatures by differential scanning calorimetry (DSC) and the texture of mesophases by using optical polarizing microscopy (POM).The target compounds showed significant liquid crystal properties.Keywords: Nematic liquid Crystal, benzylidenaminoterephthalamides.